2010
DOI: 10.1007/s11852-010-0090-7
|View full text |Cite
|
Sign up to set email alerts
|

Coastal inundation in the north-eastern mediterranean coastal zone due to storm surge events

Abstract: Low-elevation coastal areas and their populations are at risk during and after the appearance of a storm surge event. Coastal flooding as a result of storm surge events is investigated in this paper for a number of areas around the north-eastern (NE) Mediterranean coastal zone (Adriatic, Aegean and north Levantine seas). The sea level rise (SLR) due to storm surge events is examined for the period 2000-2004. Wind data, atmospheric pressure and wave data for this period as well as in situ sea elevation measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 17 publications
3
30
0
Order By: Relevance
“…According to Makris et al [36], in these two regions, the Storm Surge Index (SSI) presents the highest values underling the vulnerability of these coastal areas. Moreover, Krestenitis et al [37] showed that the southeastern Aegean Sea presents an increase of the frequency of Sea Level High (SLH) during the recent years.…”
Section: Discussionmentioning
confidence: 99%
“…According to Makris et al [36], in these two regions, the Storm Surge Index (SSI) presents the highest values underling the vulnerability of these coastal areas. Moreover, Krestenitis et al [37] showed that the southeastern Aegean Sea presents an increase of the frequency of Sea Level High (SLH) during the recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous numerical models have been developed and applied to simulate hurricane/typhoon-induced storm surges [6][7][8][9][10][11][12][13][14]. Sheng et al [15] reported that the accuracy of a storm surge simulation depends on many factors including the input data (e.g., bathymetry, topography, and wind/pressure fields), the representation of important processes (e.g., flooding and drying and bottom friction), the model grid resolution, and the open boundary conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Xie et al [20] used a three-dimensional storm surge model to study the effect of the asymmetric structure of a hurricane wind field on the storm surge and the inundation extent. Krestenitis et al [13] used a two-dimensional hydrodynamic model to investigate coastal flooding resulting from storm surge events around the northeastern Mediterranean coastal zone. Lewis et al [21] developed a computationally inexpensive inundation model from freely available data sources to estimate the flood risk from storm surges in the northern Bay of Bengal.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent study has suggested substantial changes in the return periods of ESLs for the E. Mediterranean for the end of the 21st century, with the current 1000-year event projected to occur every five years (Vousdoukas et al, 2017). Regarding the storm surges in the Aegean archipelago, these are relatively small (heights of up to about 0.5 m, Krestenitis et al, 2011) and projected to show (generally) small height increases until 2050 as well as changes in their temporal distribution (e.g., Marcos et al, 2011;Androulidakis et al, 2015;Vousdoukas et al, 2016a).…”
Section: Mean and Extreme Sea Levelsmentioning
confidence: 99%